Perancangan Tungku Pembakar Logam - Pratama, Hardian; Abu , Risal; Zulkarnain, Zulkarnain; Mukhnizar, Mukhnizar; Azman, Azmil (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
The design of this metal burning stove was made to speed up and make it easier for blacksmith craftsmen to produce quality products. Using this tool, blacksmith craftsmen can produce a stable flame in the metal burning process. Where the planning for a metal burning stove uses coal as the main fuel, because coal can produce a longer lasting fire compared to charcoal or firewood. The working principle of this metal burning stove is to use a machine tool that is driven by a blower to increase or enlarge the air or gas pressure that will transmit to the connecting pipe, and produce a stable fire so that combustion is faster and more efficient. The metal burning furnace planning process consists of: Power planning in the metal burning furnace planning p_d = 0.3 Kw, using a blower with a rotation of 2800 rpm, using 2 pipes as air conductors, the furnace volume is 7,385.28 m^3 and using a C18 castabble, weight 25 kg, cement resistance capacity 1800?.